Sustainable biobanks: a case study for a green global bioethics. Issue 1 (31st December 2022) - Samuel, G.; Lucivero, F.; Lucassen, A. M.
ABSTRACT: This paper argues that as we move to redefine global bioethics, there is a need to be attentive to the ethical issues associated with the environmental sustainability of data and digital infrastructures in global health systems. We show that these infrastructures have thus far featured little in environmental impact discussions in the context of health, and we use a case study approach of biobanking to illustrate this. We argue that this missing discussion is problematic because biobanks have environmental impacts associated with data and digital infrastructures. We consider several ethical questions to consider these impacts: what ethical work does the concept of environmental sustainability add to the debate; how should this concept be prioritised in decision-making; and who should be responsible for doing so? We call on global bioethics to play a role in advancing this dialogue and addressing these questions.